Transferência de fósforo por escoamento superficial devido à aplicação de água residuária da suinocultura e à adubação mineral em solo com diferentes declividades sob condição de chuva simulada - Dieter, Jonathan (2013)
Swine wastewater application (SWW) in soils under no-tillage system can result in increased levels of phosphorus on soil surface layers, reducing the transferring risk via runoff into the aquatic environment. This trial aimed at evaluating, in two periods of soybean cropping, phosphorus transportation with the drained surface due to SWW application and mineral fertilization (MF) to a soil under no-tillage system with different declivities (i) and submitted to the simulation of different rain intensities (Ip). The trial was carried out on a Eutrophic Red Latosol. The study consisted in applying SWW doses (0, 75, 150, 225 and 300 m3.ha-1) with MF doses of (0%, 25%, 50%, 75% and 100% recommended to the crop) on 0.70 m2 soil plots with different declivities (i) (4, 9, 14, 19 and 24%) followed by the Ip simulation (45, 60, 75, 90 and 105 mm h-1) in two periods just after fertilizer application and seeding (AFAP) and after soybean harvest (ASH). After the runoff, it was simulated the Ip during 72 minutes by collecting independent samples drained solution at intervals of 24 minutes. The concentrations of total phosphorus (Pt), particulate phosphorus (Pp) and soluble phosphorus (Ps) were determined based on the collected samples. The central composite rotational design (CCRD) was used in a complete factorial design 24, with axial points (α = (2n)1/4), totaling 28 essays analyzed as a repeated measure along time. It was observed that concentrations of Pt, Ps and Pp in the runoff solution were positively influenced and showed the following order ARS> i> Ip. The multiple linear regression models adjusted for Ps and Pp concentrations in the runoff solution showed that SWW enhances the Ps transferring to the aquatic environment, while the factors that influence the transportation (i and Ip) showed greater importance in the concentration of transported Pp. During runoff, it was observed that the highest concentrations of Pt, Ps and Pp occurred at the beginning of runoff from the AFAP period, whose Pt concentrations reduced nearly 0.45 mg.L-1 during the ASH period. SWW application enhanced phosphorus transportation through runoff and reached higher concentrations when compared to those established ones by law. Thus, it represents a potential contamination to the environment